Description of Laccomimus gen. n. and eleven new species from the Neotropical region (Coleoptera, Dytiscidae, Laccophilinae) - Toledo, Mario (2015)
A new genus of laccophiline diving beetles, Laccomimus gen. n., is here described on the basis of a large number of specimens from various collections formerly misidentified as members of the Neotropical genus Laccodytes Régimbart, 1895. Except for similar size, however, the new genus is not closely related to Laccodytes. Instead, it seems to be sister to the Oriental genus Laccosternus Brancucci, 1983, both sharing a similar body size and shape, characters of the female genital structures, and shape of the prosternal process. Twelve species are recognised within Laccomimus, all new to science except Laccomimus pumilio (LeConte, 1878) comb. n., the type species. The new species are: Laccomimus alvarengi sp. n., L. amazonas sp. n., L. bolivari sp. n., L. bordoni sp. n., L. distinctus sp. n., L. improvidus sp. n., L. malkini sp. n., L. spangleri sp. n., L. spinosus sp. n., L. variegatus sp. n., L. youngi sp. n. The distribution of the new genus includes most of the Neotropics, with one species, L. pumilio, reaching Florida, USA. Each taxon is described and illustrated and a key for their identification is provided. Laccomimus is a widespread and relatively common genus in tropical America, the species of which have a wide distributional range, except for a few confined to more restricted areas. In spite of this, Laccomimus is a very uniform genus in body shape, size and colouration, and in most cases identification of the species is possible only after examination of the male genitalia. A key to distinguish genera of the tribe Laccophilini is also presented.